KESIAPAN GURU BAHASA INDONESIA SMP DALAM IMPLEMENTASI KURIKULUM 2013 - Setyawan Pujiono (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe the readiness of teachers at junior high schools (JHSs) in theimplementation of Curriculum 2013. The readiness comprises their understanding of thecurriculum and abilities to prepare learning kits, design the syllabus, and develop learningmaterials. This was a descriptive study employing the survey approach. The researchsubjects were Indonesian language teachers at JHSs in Kulonprogo Regency. The datawere collected through a questionnaire and were descriptively analyzed using categoriesbased on each characteristic. The results show that Indonesian language teachers at JHSsare ready to implement Curriculum 2013. This is indicated by: (1) their understanding ofthe curriculum contents (68.91%), (2) their readiness in lesson planning (68.69%), (3) theirreadiness in learning implementation (72.67%), and (4) their understanding of evaluationand learning mastery (67.83%). The improvement of the readiness in the implementationof Curriculum 2013 is made through intensifying socialization, enriching supplementarymaterials, and attending training on lesson plan designs.